SWOT: IMPLEMENTASI APLIKASI MOBILE BANKING TERHADAP KUALITAS LAYANAN BANK MUAMALAT - Abdul Muthalib; Asyari Hasan (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2023)
This research identifies the advantages and disadvantages of using mobile banking in Islamic banking services, and looks for opportunities and threats that may arise as a result of the use of this technology. The purpose of the study was to analyze the implementation of mobile banking applications on the quality of Bank Muamalat's services using a SWOT analysis approach. Descriptive qualitative research methods, using primary and secondary data, provide a comprehensive overview of the strengths, weaknesses, opportunities, and threats associated with the use of mobile banking in Islamic banking services. Research shows that the use of mobile banking has great potential in improving the quality of Islamic banking services. The advantages found include efficiency, ease of access, low operational costs, and 24-hour service accessibility. However, there are also disadvantages such as reliance on a good internet connection, the risk of digital crime, and additional costs. This research makes an important contribution in understanding the factors that influence the implementation of mobile banking in the quality of Bank Muamalat KC's services. Pontianak.